The Dynamic Character Impressions Regarding the Life and Person of Thomas "Indian Warner" - Mollie Sheptenko (Caribbean Studies Students' Union, 2020)
"The Dynamic Character of Impressions Regarding the Life and Person of Thomas 'Indian' Warner," is an analysis of the "The Case of 'Indian' Warner," a part of the wider anthology Wild Majesty: Encounters With Caribs from Columbus to the Present Day by Peter Hulme and Neil Whitehead. This analysis looks to understand how the mixed Kalinago Dominican*/British heritage of Antiguan-born Thomas 'Indian' Warner was manipulated by European powers to serve their colonial pursuits whilst maintaining positive imperial/indigenous relations in the Lesser Antilles. The analysis also explores abuses of indigenous populations in the Greater Antilles by Spanish colonizers known as conquistadores.